Hakikat Pendidikan Tinggi Islam Negeri (STAIN, IAIN, UIN) dan Swasta dalam Perspektif Filsafat Pendidikan Barat dan Islam - Khubby Mulyono; Nashrullah (Al-Kindi, 2026)
The institutional transformation of Islamic Higher Education (Pendidikan Tinggi Keagamaan Islam/PTKI) from State Institutes of Islamic Studies (STAIN) and State Islamic Institutes (IAIN) into State Islamic Universities (UIN) marks a fundamental shift in the epistemological landscape of Islamic education in Indonesia. This phenomenon generates a dialectical tension between the pragmatic demands of modernity faced by state PTKI and the preservation of turāth traditions that remain dominant in private Islamic higher education institutions (PTKIS). This article aims to examine the ontological and axiological essence of these institutions through a comparative analysis of Western and Islamic philosophies of education. Employing a qualitative method with a library research approach and philosophical analysis, the study finds the existence of an existential dualism within PTKI. The findings indicate that: (1) in terms of management and the structure of science curricula, UINs tend to adopt Western pragmatism oriented toward the market and managerial efficiency; (2) conversely, in terms of ethical substance and ultimate goals, PTKI continue to strive to maintain Islamic essentialism aimed at forming the Insān Kāmil; and (3) PTKIS play a crucial role as guardians of tradition, balancing the euphoria of scientism within UINs. The article concludes that the integration of knowledge (Wahdat al-ʿUlūm) in UINs still faces challenges of latent secularization, thus requiring a renewed strengthening of adab-based curricula and synergy with the pesantren educational model.